Pengaruh Kepemimpinan Distribusi Kepala Sekolah dan Kepemimpinan Guru terhadap Mutu Pendidikan Sekolah Dasar - Yasrizal, Yasrizal; Dahlan, Jarnawi Afgani; Chandrawati, Titi (Lentera: Jurnal Ilmiah Kependidikan, 2022)
This study aims to analyze the influence of distributional leadership of principals and teacher leadership on the quality of elementary school education in Batu Besar Village, Nongsa District, Batam City. The research method uses a quantitative approach with the nature of the research being associative. The number of samples was calculated using cluster random sampling technique as many as 76 respondents. The data collection method was carried out by distributing a questionnaire with a five-point Likert scale as a measuring tool. The data analysis method used is descriptive statistics, prerequisite analysis test and statistical analysis for hypothesis testing with SPSS IBM version.24.0. Based on the results of research conducted by the distribution leadership of the principal, the t value of -0.120 has no significant effect on the quality of school education. Teacher leadership with a t-count value of 8.978 and a t-table value of 1.9939 that there is a significant influence of teacher leadership on the quality of school education. The distribution leadership of school principals and teacher leadership together has a significant influence on the quality of school education in Batu Besar Village, Nongsa District, Batam City by 56% and the remaining 34% is influenced by other factors.